Chiral representation of the nucleon mass at leading two-loop order - Ze-Rui Liang; Han-Xue Chen; Feng-Kun Guo; Zhi-Hui Guo; De-Liang Yao (Journal of High Energy Physics)
Abstract We calculate the nucleon mass in a manifestly relativistic baryon chiral perturbation theory up to the leading two-loop order. Through dimensional counting analysis, we perform the chiral expansion and verify the validity of the extended-on-mass-shell scheme at the two-loop level. As a result, we obtain the complete chiral representation of the nucleon mass up to O $$ \mathcal{O} $$ (p 5), which preserves the original analytic properties and satisfies the correct power counting. The obtained chiral result is well-suited for chiral extrapolation and provides an excellent description of lattice QCD data across a broad range of pion masses. We find that the O $$ \mathcal{O} $$ (p 5) contribution is small, approximately 10 MeV, and varies only mildly with increasing pion mass, demonstrating good convergence of the nucleon mass up to pion masses of about 350 MeV at two-loop order.